Timbre differences of an individual voice in solo and in choral singing - ŁĘTOWSKI, Tomasz; ZIMAK, Lidia; CIOŁKOSZ-ŁUPINOWA, Halina (Archives of Acoustics, 1988)
The object of the study was to analyze differences between solo and choral production of the same singer. Six female and six male chorus singers sang the same musical material solo, in vocal groups, and as a choir. Choral productions of the individual singers were obtained by recording their solo productions made under playback of the choir sound. Spectral analysis and listening tests were used to analyze differences between recorded samples. The results showed highly significant differences between both types of vocal production. The difference increased with the increasing degree of vocal training of the performer.